2006
DOI: 10.3184/030823406776330882
|View full text |Cite
|
Sign up to set email alerts
|

Ligands Containing of a C=O and an –Nh–R Adjacent to the Oxime Group and their Cobalt(Ii), Nickel(Ii) and Copper(Ii) Complexes

Abstract: Ligands having a C=O group and an -NH-R group adjacent to the oxime group have been prepared from ω-chloroisonitrosoacetophenone and aniline or aniline derivatives in the presence of NaHCO 3 . The Ni(II), Cu(II) and Co(II) complexes of the synthesised ligands have been prepared and characterised. The ligands are proposed to coordinate to the metal ions via the oxime oxygen and amide nitrogen atoms. Thermal analyses data reveals that the water in the complexes is non-coordinated to the metal ions. Binuclear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…In this assay, oximes are interfered with the formation of Fe 2+ and Fe 3+ -complex since they have chelating activity to capture Fe 2+ ion before ferrozine (oxime + Fe 2+ → oximeFe 2+ complex). The oxime ligands are good chelating agents for metal ions [1,27]. The metal chelating effects of the oximes were found as concentration-dependent.…”
Section: Antiradical Activitymentioning
confidence: 94%
See 3 more Smart Citations
“…In this assay, oximes are interfered with the formation of Fe 2+ and Fe 3+ -complex since they have chelating activity to capture Fe 2+ ion before ferrozine (oxime + Fe 2+ → oximeFe 2+ complex). The oxime ligands are good chelating agents for metal ions [1,27]. The metal chelating effects of the oximes were found as concentration-dependent.…”
Section: Antiradical Activitymentioning
confidence: 94%
“…The syntheses of the oxime derivatives 1-5, 7-10 used in this work, have been described previously by Tas and et al [27,[36][37][38][39][40][41][42]. Compound 6 was newly prepared for this work from the reaction of -chloroisonitrosoacetophenone with 3,4 dimethylaniline using Tas' method [27].…”
Section: Synthesis Of the Oximesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Previous works reported that oxime derivatives possessed insecticidal, miticidal, nematocidal, antiradical, antioxidant, antiepileptic, antihyperglycemic, antimicrobial, antidote, anticarcinogenic and anti-HIV activities. [7][8][9][10][11][12][13][14][15][16][17][18] We synthesized a series of novel phenylacetamidine based amido-carbonyl oximes (C1-C9). Structures of the compounds characterized by 1 H-NMR, IR spectroscopy, and X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%